Heterogeneous integration of amorphous silicon carbide on thin film lithium niobate - Zizheng Li; Naresh Sharma; Bruno Lopez-Rodriguez; Roald van der Kolk; Thomas Scholte; Hugo Voncken; Jasper van der Boom; Simon Gröblacher; Iman Esmaeil Zadeh (APL Photonics)
In the past decade, lithium niobate (LiNbO3 or LN) photonics, thanks to its heat-free and fast electro-optical modulation, second-order non-linearities, and low-loss, has been extensively investigated. Despite numerous demonstrations of high-performance LN photonics, processing lithium niobate remains challenging and suffers from incompatibilities with standard complementary metal–oxide–semiconductor (CMOS) fabrication lines, limiting its scalability. Silicon carbide (SiC) is an emerging material platform with a high refractive index, a large non-linear Kerr coefficient, and a promising candidate for heterogeneous integration with LN photonics. Current approaches of SiC/LN integration require transfer-bonding techniques, which are time-consuming, expensive, and lack precision in layer thickness. Here, we show that amorphous silicon carbide (a-SiC), deposited using inductively coupled plasma enhanced chemical vapor deposition at low temperatures (<165 °C), can be conveniently integrated with LiNbO3 and processed to form high-performance photonics. Most importantly, the fabrication only involves a standard, silicon-compatible, reactive ion etching step and leaves the LiNbO3 intact, hence its compatibility with standard foundry processes. As a proof-of-principle, we fabricated waveguides and ring resonators on the developed a-SiC/LN platform and achieved intrinsic quality factors higher than 1.06 × 105 and a resonance electro-optic tunability of 3.4 pm/V with a 3 mm tuning length. We showcase the possibility of dense integration by fabricating and testing ring resonators with a 40 μm radius without a noticeable loss penalty. Our platform offers a CMOS-compatible and scalable approach for the implementation of future fast electro-optic modulators and reconfigurable photonic circuits, as well as nonlinear processes that can benefit from involving both second- and third-order nonlinearities.